Product ion filtering with rapid polarity switching for the detection of all fumonisins and AAL‐toxins. (14th October 2015) - Renaud, Justin B.; Kelman, Megan J.; Qi, Tianyu F.; Seifert, Keith A.; Sumarah, Mark W.
<x xml:space="preserve">Abstract</x> Rationale Fumonisins and AAL‐toxins are structurally similar mycotoxins that contaminate agricultural crops and foodstuffs. Traditional analytical screening methods are designed to target the known compounds for which standards are available but there is clear evidence that many other derivatives exist and could be toxic. A fast, semi‐targeted method for the detection of all known fumonisins, AAL‐toxins and related emerging toxins is required. Methods Strains of Fusarium verticillioides, Alternaria arborescens and Aspergillus welwitschiae were grown on their associated crops (maize, tomatoes, and grapes, respectively). Extracts were first analyzed in negative mode using product ion filtering to detect the tricarballylic ester product ion that is common to fumonisins and AAL‐toxins (m/z 157.0142). During the same liquid chromatography (LC) run, rapid polarity switching was then used to collect positive mode tandem mass spectrometric (MS2) data for characterization of the detected compounds. Results Fumonisin B1, B2, B3 and B4 were detected on Fusarium contaminated maize, AAL‐toxins TA, TB, TD, TE were detected on Alternaria inoculated tomatoes and fumonisin B2, B4 and B6 on Aspergillus contaminated grapes. Additionally, over 100 structurally related compounds possessing a tricarballylic ester were detected from the mould inoculated plant material. These included a hydroxyl‐FB1 from F. verticillioides inoculated maize, keto derivatives of AAL‐toxins from A. arborescens inoculated tomatoes, and two previously unreported classes of non‐aminated fumonisins from Asp. welwitschiae contaminated grapes. Conclusions A semi‐targeted method for the detection of all fumonisins and AAL‐toxins in foodstuffs was developed. The use of the distinctive tricarballylic ester product anion for detection combined with rapid polarity switching and positive mode MS2 is an effective strategy for differentiating between known isomers such as FB1 and FB6. This analytical tool is also effective for the identification of new compounds as evident from the discoveries of the previously unreported hydroxyl‐FB1, keto‐AAL‐toxins, and the two new families of non‐aminated fumonisins. © 2015 Her Majesty the Queen in Right of Canada Rapid Communications in Mass Spectrometry © 2015 John Wiley & Sons Ltd. Reproduced with the permission of the Ministers of Agriculture and Agri‐Food Canada.